2019
DOI: 10.1158/1055-9965.epi-18-0629
|View full text |Cite
|
Sign up to set email alerts
|

Low Rates of Patient-Reported Physician–Patient Discussion about Lung Cancer Screening among Current Smokers: Data from Health Information National Trends Survey

Abstract: Background: Many professional societies published guidelines recommending lung cancer screening with lowdose CT scan. We examined the temporal trends in patientreported physician-patient discussions about lung cancer screening, and aimed to determine the association of discussions of lung cancer screening with the smokers' attempt to quit and intent to quit.Methods: Data from years 2012, 2014, and 2017 of the National Cancer Institute's Health Information National Trends Survey (HINTS) were combined to create … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 20 publications
0
10
3
Order By: Relevance
“…Over half (53%) of the participants in this study reported having talked to their healthcare provider about lung cancer in the past year, which is considerably higher than what has been reported in prior research (Carter-Harris et al 2016;Huo et al 2019). Current and former smokers, and participants reporting less than a 30 pack-year (PPY) smoking prevalence, being outside of the 55-80 years old eligibility age-range, and identifying as male had greater odds of talking to a healthcare provider in the past year about lung cancer screening.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…Over half (53%) of the participants in this study reported having talked to their healthcare provider about lung cancer in the past year, which is considerably higher than what has been reported in prior research (Carter-Harris et al 2016;Huo et al 2019). Current and former smokers, and participants reporting less than a 30 pack-year (PPY) smoking prevalence, being outside of the 55-80 years old eligibility age-range, and identifying as male had greater odds of talking to a healthcare provider in the past year about lung cancer screening.…”
Section: Discussioncontrasting
confidence: 56%
“…Participants with any history of smoking tobacco and reporting less than a 30 pack-year (PPY) smoking tobacco prevalence had high odds of talking with their healthcare provider about lung cancer screening in the past year. This is unique to prior research examining US population-based surveillance data, which found that being a current smoker increases the likelihood of having talked to a healthcare provider about lung cancer in the past year (Carter-Harris et al, 2016;Huo et al, 2019). Once controlling for the perceived availability of online instrumental and emotional support, however, results demonstrated that identifying as a current smoker, male, and living with COPD increased the odds of these clinical conversations in the past year.…”
Section: Principal Findingscontrasting
confidence: 48%
See 1 more Smart Citation
“…Evidence-based tobacco cessation interventions in the 2008 U.S. Public Health Service clinical guidelines and The Community Guide include advising patients to quit smoking, providing cessation counseling and medications, and connecting patients to other cessation resources such as 1-800-QUIT-NOW (6). Recent studies suggest that training primary care providers on how to conduct shared decision-making discussions and implement effective smoking cessation interventions in the context of lung cancer screening is needed (7,8).…”
Section: Discussionmentioning
confidence: 99%
“…Despite this five-step guideline, and studies showing positive effects of a provider’s discussion in helping smokers quit, the uptake of provider–patient discussion remains suboptimal [ 1 , 5 ]. Based on nationally representative samples from the National Health Interview Survey (NHIS), the prevalence of provider–patient discussion about smoking (the first A: ask) ranged from 51.3% in 2011 to 55.4% in 2015 [ 6 , 7 ]. The prevalence of patient–provider discussion on quitting (the second A: advise) ranged from 53.3% in 2000, and 58.9% in 2005, to 50.7% in 2010, and was 57.2% in 2015 [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%